Plant growth habit, root architecture traits and tolerance to low soil phosphorus in an Andean bean population - Cichy, Karen Ann; Snapp, Sieglinde S.; Blair, Matthew W. (Springer, 2009)
The optimal plant growth habit and architecture of common bean (Phaseolus vulgaris L.) is dependent on environmental conditions. The objectives of this research were to determine if plant growth habit impacts a plant s ability to grow in low P conditions, as measured by P uptake, seed yield, and P use efficiency and to determine if aboveground plant growth habit and root growth are associated at variable P soil levels. The study was carried out with recombinant inbred lines developed from an Andean intra-gene pool cross between a low P tolerant parent with an indeterminate growth habit (G19833) and a low P susceptible parent with a determinate growth habit (AND696). The population was grown for 2 years in low and sufficient P conditions in a field site in Darien, Colombia. In the first season, indeterminate lines had 15% more seed yield than the determinate lines in the low P treatment, whereas there was no difference by growth habit in the high P treatment. In the second season, seed yield and tolerance to low P was not influenced by growth habit. Root architectural characteristics such as root length density (RLD) and root surface area were 25% and 34% greater respectively in the indeterminate lines under P-sufficiency, whereas under low P, root architecture traits were not significantly different by growth habit. Root plasticity was higher in determinate lines, although RLD and root surface area did not play a significant role in tolerance to low P. Overall, the data were consistent with shoot growth habit as playing a complex and important role in adaptation to P-deficiency.